PRAKTIKUM FISlKA DENGAN MENGGUNAKAN LKS COMPETENCE BASED PROCESS SKILLS SEBAGAI ALAT EVALUASI - Isaak H. Weno (Universitas Negeri Yogyakarta, 2008)
The aim of learning and teaching process are depends on involve betwen teacher and student andfasility that are same with combined in material was learned. In thephysics learning, it is usuallyused by TPK with eksperimental method there is a skill process approach used by teacher to increase the student learning result. The TPK are purposeses to make the student exercise learn in groups, and make teacher easy to look for personal student ability. To evaluate stutent ability, the method used are discriftif method applied with LKS (Student Work Sheet) is prepared by researcher and all laboratory equipments, than students try to arrange the eksperimental design according to the instructions. This researchfound that all of laerning result of students are 85 %. It means that TPK as an evaluation instrument of skill process approach developed by teacher, can be optimalisation as an intruments ofstudent learning assesment. Finally, this research conclude that student skill process can be increase rapidly in the short time of alllearningprocess